The Latest Armed and Political Movement for the Independence of Ukraine - Vovk, Oleksandr (Genocidas ir rezistencija, 1997)
Banderites are the name given to the fighters for Ukraine’s independence in western Ukraine in 1940s and 1950s. The organised nationalist movement was so violent and numerous that the occupiers continue to this day identify every unfavourable Ukrainian with this movement. Heavy casualties and the long period of struggle show that the movement for independence and the armed resistance against the invaders in western Ukraine were massive and widely supported by Ukrainians. The memories of that armed struggle had a strong influence on the course of events in Ukraine until 1991, when the process of ‘transformation’ resulted in the restoration of Ukrainian independence.
Keywords: Ukraine; antisoviet resistance; Ukraine nationalist organization; Poland